Glass medium doped rare earth for sensor material. (2018) - Djamal, M.; Yuliantini, L.; Hidayat, R.; Boonin, K.; Yasaka, P.; Kaewkhao, J.
Abstract: Nowadays, research on sensor materials become more intensive due to the benefit of the sensor for human life. Recently, glass medium doped rare earth ion has been investigated for some applications, e.g. laser, LED, optical amplifier, and some others. However, its application for sensor material is still limited. Experimental results showed that the glass medium doped rare earth ion has good potential for sensor applications, such as for radiation and temperature measurement. The addition of dopant improved the glass structure. In this paper, characterization of optical and photoluminescence properties of glass medium doped rare earth for sensor applications was observed.